Leadership styles of executives in team sports - Maksimovic, N.; Milosevic, Z.; Matic, R.; Obradovic, B. (2nd International scientific conference: Exercise and quality of life, Novi Sad. March 24/26th 2011, 2011)
Leadership style refers to characteristics the way an individual leads others. Connection between leadership style and efficiency of sport organizations, has been confirmed in many studies. The aim of this study was to determine the leadership styles characteristics of executives in sports clubs in team sports (football, basketball, volleyball, handball and water polo). For information collecting MLQ questionnaire is used (Multifactor Leadership Questionnaire) with 45 items, with an inventory of the respondents leadership style characteristics. The sample of respondents included 179 executives from 119 organized sports clubs in Serbia in team sports (football, basketball, handball, volleyball and water polo), for who the scores achieved on the MLQ scale were calculated. By comparing the results (Means) for all leadership factors, it is evident that respondents in all sports achieve higher scores in the transactional in relation to transformational leadership.